Chemical Nature of Soda Lignins and Pulp Sheet Properties of Indian Bamboos - Singh, Man Mohan; Bhola, P. P. (Indian Forester, 1978)
The lignin content of different species of bamboo of Indian origin varies within narrow limits of 24±3%. The carbon and hydrogen content of these lignins are 59.7±3% and 6.3±0.5% respectively. The number of C9 units varies from 12 to 21 with an average of 14 indicating that the structure of bamboo lignin skeleton is more akin to hardwoods than conifers. The I.R. Spectra of all these is similar and show that bamoo lignin is composed of polymer of mainly propyl guaiacyl, propyl syringyl, as well as p-hydroxy benzal. There is a correlation between the number of C9 units of different bamboos and breaking length of the beaten pulps.